Radiological Characteristics and Clinical Outcome of Ossification of Posterior Longitudinal Ligament Involving C2 After Posterior Laminoplasty and Instrumented Fusion Surgery. Issue 3 (1st February 2019) - Wang, Liang; Jiang, Yunpeng; Li, Mu; Si, Haipeng; Li, Le; Qi, Lei
Abstract : Study Design: Retrospective study. Objective: To analyze the radiological characteristics and surgical outcome of cervical ossification of posterior longitudinal ligament (OPLL) involving C2 level. Summary of Background Data: The study and report focused on the OPLL involving C2 level are rare. Therefore, the radiological characteristics and surgical outcome remain unclear. Methods: The records of the patients with OPLL involving C2 level who underwent posterior surgery from July 2006 through October 2015 were retrospectively reviewed. The types, longitudinal and transverse extent, occupation ratio, K-line classification of OPLL, and high-intensity zone of spine cord on magnetic resonance imaging were analyzed to evaluate the radiological characteristics. All the cases received posterior open-door laminoplasty and instrumented fusion surgery. The Japanese Orthopedic Association (JOA) score and recovery rate (RR) were used to evaluate neurological function after surgery. Results: A total of 45 patients with OPLL involving C2 level were enrolled in the study. Their radiological data were carefully analyzed. The mixed (73.3%) and continuous type (24.5%) were observed. The mean number of involved segments was 5.1. The narrowest spinal canal mostly located in the level of C3-C4 and mean occupying ratio was 65.3%. Thirty-two patients were followed up for at least 2 years and the mean follow-up time was 46.2 months. The mean JOA score was 10.3 preoperatively and 15.2 at the final follow-up and the mean RR was 70.7%. The K-line (+) and (−) subgroups showed similar preoperative JOA score and RR. The high-intensity zone (+) subgroup showed lower preoperative JOA score but equal RR with (−) subgroup. Conclusion: When OPLL involve C2 level, it often presented different radiological characteristics. The posterior open-door laminoplasty and instrumented fusion surgery could achieve favorable clinical outcomes. Further researches and long-term clinical follow-up are needed to better appreciate the OPLL involving C2 level. Level of Evidence: 4 Abstract : The retrospective study was made to analyze the radiographical characteristics and surgical outcome of ossification of posterior longitudinal ligament (OPLL) involving C2 level. These OPLL was mostly mixed or continuous type, involving long segments and the narrowest spinal canal mostly located in C3-C4. The posterior laminoplasty and instrumented fusion could achieve favorable clinical outcomes.